Estimasi Emisi Gas Rumah Kaca dari Proses Pengelolaan Sampah Di Tempat Pemrosesan Akhir (TPA) Kabupaten Kerinci - Winny Laura Christina Hutagalung; Elda Ariska; Rinaldi Rinaldi (Jurnal Daur Lingkungan, 2023)
The amount of waste that enters the TPA of Kerinci Regency in 2020 is 21,962 Gg/year. The waste that enters the TPA is predicted to produce greenhouse gas emissions in the form of CH4, N2O and CO2. This study aims to determine the amount of generation and type of waste composition and calculate the estimated amount of greenhouse gas emissions (CH4, N2O, and CO2) in the TPA Kerinci until 2030. The calculation of GHG emissions used in this study is to use the Intergovernmental panel on climate change (IPCC) 2006. The composition of waste produced from TPA Kerinci Regency consists of 14.37% plastic waste, 15.50% Nappies waste, 2.47% textile waste, 1.86% metal waste, 2.98% wood waste, 39.93% food waste, 10.12% garden and plant waste, 7.46% paper and cardboard waste, 1.61% rubber and leather waste, 0.55% glass waste, and 3.11% other waste. In the waste management process, the emissions generated from the landfill zone, composting and heavy equipment produced in the TPA Kerinci Regency are 0.496 Gg CO2-eq, while in 2030 the resulting emissions will increase by 16.55 Gg CO2-eq. GHG emission estimation can be used to determine methods of mitigating greenhouse gas emissions.